Favorable Outcomes of Anticoagulation With Unfractioned Heparin in Sepsis-Induced Coagulopathy: A Retrospective Analysis of MIMIC-III Database - Peng, Jiang-Chen; Nie, Fang; Li, Yu-Jie; Xu, Qiao-Yi; Xing, Shun-Peng; Li, Wen; Gao, Yuan (Frontiers in Medicine, 2022)
Backgrounds: Anticoagulation in sepsis-associated disseminated intravascular coagulation (DIC) remains uncertain. The aim of this study was to investigate whether unfractioned heparin (UFH) could improve clinical outcomes in patients with sepsis-induced coagulopathy (SIC). Methods: Septic patients with SIC were identified from the Medical Information Mart for Intensive Care (MIMIC)-III database. Cox-proportional hazards model, logistic regression model and linear regression were used to assess the associations between UFH administration and 28-day mortality, hospital mortality, occurrence of bleeding complications and length of stay, respectively. Propensity score matching (PSM) analysis was used to match the imbalance between patients in the UFH group and the control group. Patients were further stratified according to SIC score and Simplified Acute Physiology Score II (SAPS II). Results: A total of 1820 septic patients with SIC were included in the data analysis. After PSM, 652 pairs of patients were matched between the patients in the UFH group and the control group. UFH was significantly associated with reduced 28-day mortality (adjusted HR, 0.323, 95% CI, 0.258-0.406; p < 0.001) and hospital mortality (adjusted HR, 0.380, 95% CI, 0.307-0.472; p < 0.001) without increasing the risks of intracranial haemorrhage (adjusted OR, 1.480, 95% CI, 0.955-2.294; p = 0.080) or gastrointestinal bleeding (adjusted OR, 1.094, 95% CI, 0.503-2.382; p = 0.820). For subgroup analysis, it didn’t change the favorable results of UFH on mortality. Conclusions: The analysis of MIMIC-III database indicated that anticoagulant therapy with UFH may be associated with a survival benefit in patients with SIC.